(4z-3)(7z+6)=

Simple and best practice solution for (4z-3)(7z+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4z-3)(7z+6)= equation:


Simplifying
(4z + -3)(7z + 6) = 0

Reorder the terms:
(-3 + 4z)(7z + 6) = 0

Reorder the terms:
(-3 + 4z)(6 + 7z) = 0

Multiply (-3 + 4z) * (6 + 7z)
(-3(6 + 7z) + 4z * (6 + 7z)) = 0
((6 * -3 + 7z * -3) + 4z * (6 + 7z)) = 0
((-18 + -21z) + 4z * (6 + 7z)) = 0
(-18 + -21z + (6 * 4z + 7z * 4z)) = 0
(-18 + -21z + (24z + 28z2)) = 0

Combine like terms: -21z + 24z = 3z
(-18 + 3z + 28z2) = 0

Solving
-18 + 3z + 28z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-6 + -7z)(3 + -4z) = 0

Subproblem 1

Set the factor '(-6 + -7z)' equal to zero and attempt to solve: Simplifying -6 + -7z = 0 Solving -6 + -7z = 0 Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7z = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -7z = 0 + 6 -7z = 0 + 6 Combine like terms: 0 + 6 = 6 -7z = 6 Divide each side by '-7'. z = -0.8571428571 Simplifying z = -0.8571428571

Subproblem 2

Set the factor '(3 + -4z)' equal to zero and attempt to solve: Simplifying 3 + -4z = 0 Solving 3 + -4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4z = 0 + -3 -4z = 0 + -3 Combine like terms: 0 + -3 = -3 -4z = -3 Divide each side by '-4'. z = 0.75 Simplifying z = 0.75

Solution

z = {-0.8571428571, 0.75}

See similar equations:

| 2z^2=z+6 | | (y/5) | | x-7=19-x | | (x^2+x^4)(x^2-y^4)=0 | | 1/3m-7=5 | | 7/2x+7=9 | | 3x/7+2=-15 | | (X+2)(x^2+5x-7)=0 | | 8(6)=(1/2)z+5 | | 2/3x-2=19 | | 2x^3+8x^2+9x+2=0 | | 8=(1/2)z+5 | | 2/3m-4=14 | | 2/3v=74 | | -13x-26=(1/2)u | | 3x.4+3=27 | | 7/p=4/p-9 | | -13=(1/2)u | | 3x.2=15 | | 3x-12/5x-20 | | a/21.23=-3.5 | | 216=x(x+6) | | -3/10z=2(1/4) | | 72=4.5 | | 320+80x=2650 | | 84=.5*21x | | 72=4.5c | | (y+1)/(y^2-y) | | .666x+5=3 | | 4/(1-x)=7/(1+x) | | x^2+y^2=29 | | 4/1-x=7/1+x |

Equations solver categories